Investigación y desarrollo de una superficie de apoyo ergonómica y dinámica, adaptable a múltiples morfologías corporales - Barbirotto, Damián (2010)
This thesis investigates the ergonomic relationship between support surfaces and people who suffer from morphological problems in the back, more specifically: kyphosis and scoliosis.\nThe research and development was based on the design of a surface for different body morphologies which can be more adaptable than conventional supports, and achieving a dynamic degree of adaptation during the movements pertaining to postural adjustments.\nDuring the thesis, we researched and submitted different design proposals to provide a solution for the above mentioned problem. Based on the selected design, we performed tests with a functional prototype to check the proposed hypothesis. \nThe preliminary conclusions based on the obtained results with the researched morphologies indicate that the proposed surface can improve the distribution of superficial pressure, the adaptation to different body morphologies and to different movements of posture, compared to a conventional seat. \nConsequently, the comfort of the users in a sitting posture can be improved with the researched body morphologies, as well as the comfort of users in general, since the proposed design improves the support of the back.